Shear strength of prestressed FRP reinforced concrete beams with shear reinforcement. (1st March 2020) - Kueres, Sophia; Will, Norbert; Hegger, Josef
Highlights: Presentation of results of shear tests conducted on concrete beams pre-tensioned with CFRP tendons. Analysis of influence of shear span-depth ratio and level of prestressing on shear strength of prestressed concrete beams. Analysis of crack formation and crack geometry of the governing shear crack observed in tests. Development of shear resistance model for prestressed FRP reinforced concrete beams with shear reinforcement. Validation of proposed shear resistance model by means of experimental test results and tests reported in literature. Abstract: To avoid brittle shear failures, the shear strength of reinforced concrete beams has to be verified at ultimate limit state. For this purpose, simple but accurate shear design provisions or shear resistance models are required. In current design provisions the influence of prestressing is either neglected or insufficiently considered in the design equations leading to rather conservative results due to the lack of investigations concerning the shear strength of FRP prestressed beams. To overcome this drawback, shear tests on concrete beams with textile shear reinforcement and pre-tensioned CFRP tendons were conducted and the results are presented in this paper. Besides the investigation of the influence of the level of prestressing and of the shear span-depth ratio on the shear strength, special attention was paid to the formation and the inclination of the shear cracks as well as the crack pattern to investigate the failure mechanism more in detail. Furthermore, theoretical investigations were conducted in order to derive a simple shear design model for prestressed concrete beams with FRP shear reinforcement. For this purpose, an existing shear resistance model based on a truss model with variable strut inclination is extended considering the beneficial effects of prestressing on shear strength.